Post occupancy evaluation (POE) on green building / Muhammad Nurfaiz Baharuddin - Baharuddin, Muhammad Nurfaiz (Faculty Architecture, Planninng and Surveying, 2015)
The aim of this research is to identify building functional performance and evaluate the green building in Malaysia through the Post Occupancy Evaluation (POE) concept. This research will determine the user’s satisfaction on the green building that the occupants live in there and the owners of the building will know the satisfaction for every occupants also. There have been limited studies to conduct this research and it have some limitation for researcher to complete this research such as difficult to access the case study, lack of cooperation from certain department and the collection of data and the security tightly. Commonly, the green building system is still new in Malaysia and it must been evaluate through this evaluation to know the satisfaction of users for the implementation of green building. On this research the researcher collect the data from the questionnaire and also from the structure interview and specific for the important person. The significance of this research will gives the acknowledgement and also the benefits of user’s satisfaction to the owners of the green building about these implementation to make it some improvements and adjustments about the equipment of green building.